Ethnomusicology and Performance Studies: Towards Interdisciplinary Futures of Indian Classical Music - Prasad, Pavithra; Roy, Jeff (MUSICultures, 2018)
Abstract: Using Indian classical music as a site of transparency, the authors critically examine how the fields of ethnomusicology and performance studies approach performance. Responding to the (dis)placement of music scholarship within the framework of virtuosity, the authors treat generational frictions that exist between their disciplines not as oppositional or antagonistic, but as opportunities to maximize scholarly engagement between both fields. The authors propose de-centering music scholarship from traditional milieux of authority, in an effort to contextualize imperfect participatory performances of multiculturally emplaced subjects and scholars. This essay is concluded with some pragmatic directions that come out of the critiques highlighted therein.